2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--30139
|View full text |Cite
|
Sign up to set email alerts
|

Board 93 : Ten Ways Academic Libraries Can Help their Departments Increase Retention of Women Engineering Students

Abstract: is an Associate Engineering Librarian at the University of Florida (UF). She assists students with research, data support, and citation management. She investigates and integrates creative technologies, such as 3D printing into the STEM discipline library services. She has a BS in chemical engineering and MS in environmental engineering from UF, over 20 years of experience in industry and consulting, and is a licensed professional engineer in Florida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…In this sense Blosser (2017) pointed out that faculty tend to classify disciplines as feminine or masculine. Agricultural, biological, biomedical, and environmental engineering seem to be socially relevant (Bossart and Bharti 2018), which are supposed to attract female students, while other degrees, classified as dirty or more technical, are supposed to be less appealing for women. As a result, the language used by teachers to describe their disciplines can have a negative influence in the cultural knowledge about gender and professional careers and prevent women's enrollment in engineering.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense Blosser (2017) pointed out that faculty tend to classify disciplines as feminine or masculine. Agricultural, biological, biomedical, and environmental engineering seem to be socially relevant (Bossart and Bharti 2018), which are supposed to attract female students, while other degrees, classified as dirty or more technical, are supposed to be less appealing for women. As a result, the language used by teachers to describe their disciplines can have a negative influence in the cultural knowledge about gender and professional careers and prevent women's enrollment in engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Such measures may include creating environments which encourage women to exercise their interests in engineering tasks that address societal challenges. Studies have shown that women earn larger portions of undergraduate degrees in programs which prepare them for careers that will benefit society [18]. GradWIE may seek to facilitate such environments and measure correlation with retention.…”
Section: How Survey Results Have Shaped the Group Thus Farmentioning
confidence: 99%